Upaya Lembaga Pendidikan Islam Dalam Menghadapi Tantangan Di Era Globalisasi - Maulida, Ratna Siti; Fauziah, Siti Syifa; Al Faqih, Saad; Muin, Abdul; Mu’izzuddin, Mochammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The era of globalization has brought various significant changes in people's lives, including in the field of education. Islamic education, as an education system rooted in religious values, faces complex challenges in responding to this global phenomenon. This paper aims to explore Islamic education strategies that can be applied to overcome the problems that arise due to globalization. The method used in this study is a literature study that examines literature related to Islamic education and the impact of globalization on education. The findings suggest that Islamic education needs to integrate spiritual and moral values in the curriculum, as well as utilize information and communication technologies to improve the quality of teaching. In addition, collaboration between educational institutions, families, and society is also the key to shaping the character of the younger generation who are able to compete globally without losing their identity as Muslims. Thus, the implementation of a holistic and adaptive educational strategy is expected to answer the challenges of the times and prepare individuals who are not only intellectually intelligent but also have good morals.